HOW EFFICIENT ARE MALAYSIAN PUBLIC UNIVERSITIES? A COMPARATIVE ANALYSIS USING DATA ENVELOPMENT ANALYSIS - Lim Hock-Eam; Fauziah Md. Taib; Nur Adiana Hiau Abdullah; Yen Siew Hwa (Asian Academy of Management Journal, 2016)
This paper aims to examine the efficiency of Malaysian public universities in comparison with the private and foreign universities using Data Envelopment Analysis (DEA). The study involves 22 universities (17 public, 1 private and 4 foreign) and based on data between year 2008 and 2011. Results reveal that the most efficient Malaysian public universities are: University Malaya (among research universities); Universiti Teknologi Mara (among comprehensive universities) and Universiti Utara Malaysia (among focused universities). When these three most efficient Malaysian public universities are compared with the private university in Malaysia and another 4 foreign universities, they are found to be inefficient in income generation and in managing inputs which include the government operating grant. The plausible explanation could be associated with a long history of over-dependence on government grants that may have resulted in the public universities becoming too complacent. The study calls for mechanisms to re-strategise and to get these public universities to be more financially independent.